Increased water yield due to the hemlock woolly adelgid infestation in New England. Issue 5 (15th March 2017) - Kim, Jihyun; Hwang, Taehee; Schaaf, Crystal L.; Orwig, David A.; Boose, Emery; Munger, J. William
Abstract: Over the past few decades, a hemlock woolly adelgid (HWA) infestation has significantly affected eastern hemlock ( Tsuga canadensis ) in the eastern U.S., and warmer winters are expected to promote a continued northward expansion in the future. Here we report a water yield increase due to the HWA infestation in New England, U.S. Since the first observation in 2002, peak growing season evapotranspiration over a hemlock‐dominated area has decreased by 24–37% in 2012 and 2013. Over the same time period, the water yield from the study catchment significantly increased as compared to an adjacent catchment with less hemlock cover. The net increase was estimated to be as much as 15.6% of annual water yield in 2014 based on an ecohydrological modeling analysis. This study indicates that the ongoing hemlock decline is also largely altering hydrological regimes in the northeastern U.S. Key Points: In New England, eastern hemlocks have experienced significant foliar loss due to hemlock woolly adelgid (HWA) infestation Evapotranspiration flux over a hemlock‐dominated forest has significantly decreased Water yield has increased due to the infestation, more in the catchment with a higher hemlock cover